Tomato yellow leaf curl Kanchanaburi virus Penyebab Penyakit Mosaik Kuning pada Tanaman Terung di Jawa - Tega Kintasari; Dwi Wiyati Nurul Septariani; Sri Sulandari; Sri Hendrastuti Hidayat (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Yellow and yellow mosaic symptoms was observed on eggplant (Solanum melongena) around Bogor, Bandung, Pati, Rembang, and Bantul during a survey in early 2013. Polymerase chain reaction based detection was carried out using total DNA isolated from symptomatic leaf samples and a pair of Begomovirus-universal primers, SPG1/SPG2. The expected size ( 900 bp) amplicon was detected from all five symptomatic samples, indicating the presence of Begomovirus infection. Each amplicon was sequenced followed by basic local alignment search tool analysis. It was revealed that the sequence had the highest homology (98.8%) with Tomato yellow leaf curl Kanchanaburi virus (TYLCKaV) sequence. This is the first report on TYLCKaV infection on eggplant in Indonesia.